2014
DOI: 10.1016/j.chembiol.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Maresin-like Lipid Mediators Are Produced by Leukocytes and Platelets and Rescue Reparative Function of Diabetes-Impaired Macrophages

Abstract: SUMMARY Non-healing diabetic wounds are associated with impaired macrophage (Mf) function. Leukocytes and platelets (PLT) play crucial roles in wound healing by poorly understood mechanisms. Here, we report identification and characterization of novel maresin-like(L) mediators 14,22-dihydroxy-docosa-4Z,7Z,10Z,12E,16Z,19Z-hexaenoic acids, 14S,22-diHDHA (maresin-L1) and 14R,22-diHDHA (maresin-L2) that are produced by leukocytes and PLT and involved in wound healing. We show that 12-lipoxygenase-initiated 14S-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 45 publications
6
49
0
Order By: Relevance
“…3 Subsequently, the compound was synthesized, and the structure was determined. 4 Similar properties were then found in new metabolite 2 ('maresin like'), 5 and the structure of 2 was also determined after organic synthesis as well. 6 We then envisaged that hydroxylated compound 3 would possess similar activities because of the structural similarity in the positions of the hydroxylated carbon atoms relative to those in 1 and 2.…”
supporting
confidence: 56%
“…3 Subsequently, the compound was synthesized, and the structure was determined. 4 Similar properties were then found in new metabolite 2 ('maresin like'), 5 and the structure of 2 was also determined after organic synthesis as well. 6 We then envisaged that hydroxylated compound 3 would possess similar activities because of the structural similarity in the positions of the hydroxylated carbon atoms relative to those in 1 and 2.…”
supporting
confidence: 56%
“…The main metabolite, 14-OH-22:6, has been clearly shown of interest for being the most potent to antagonize the pro-aggregatory and vaso-constricting effects of TxA 2 on platelets and smooth muscle cells, respectively [30,31]. In addition, it has been reported that some maresins from DHA (14S,22-diHDoHA (maresin-L1) and 14R,22-diHDoHA (maresin-L2)) are produced by both platelets and leukocytes, and partly responsible for reparative functions of these cells in wounds [32]. Docosapentaenoic acids, 22:5n-3 and 22:5n-6 are also good substrates of platelet 12-LOX, and the former behaves like DHA with its conversion into 11-and 14-OH derivatives, whereas 22:5n-6 is only converted into 14-OH-22:5 [33].…”
Section: Oxygenation Of Ara In Human Blood Plateletsmentioning
confidence: 99%
“…MaR-1 is effective in controlling inflammation in periodontal infections with unresolved inflammation and leukocyte-mediated tissue destruction (108), and restoring the reparative function of nonhealing diabetic wounds impaired the macrophages (109). MaR-1 has also been tested in the treatment of diabetic nephropathy by inhibiting nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing-3 and controls the inflammation rate in renal failure (110).…”
Section: Mars As Therapeutic Targetsmentioning
confidence: 99%